2014
DOI: 10.1111/1552-6909.12308
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Oral Prenatal Probiotics against Maternal Group B Streptococcus Vaginal and Rectal Colonization

Abstract: Prenatal probiotic therapy has the potential to reduce GBS colonization. The potential of the probiotic intervention appears to be linked to daily adherence. A controlled clinical trial with a larger, adequately powered sample is feasible and justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 28 publications
0
46
0
2
Order By: Relevance
“…62 Additionally, the prenatal probiotic supplementation to reduce GBS colonization has been recommended as a safe strategy, but there are not enough clinical trials to support this practice. 63,64 For example, Hanson et al 63 observed that pregnant women that were administered with oral probiotic (from the 28th week of pregnancy) had lower GBS vaginal load at 36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…62 Additionally, the prenatal probiotic supplementation to reduce GBS colonization has been recommended as a safe strategy, but there are not enough clinical trials to support this practice. 63,64 For example, Hanson et al 63 observed that pregnant women that were administered with oral probiotic (from the 28th week of pregnancy) had lower GBS vaginal load at 36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have observed an inverse correlation between levels of Lactobacillus species and GBS in the human vaginal tract (15,16). Even so, preliminary human studies with Lactobacillus probiotic treatments (16,17), as well as murine models (5), have failed to show significant reduction of GBS vaginal colonization. While this paper was being reviewed, a recent study was published that showed reduction of GBS vaginal load in mice, but only if Lactobacillus was given prior to GBS colonization (18).…”
Section: Discussionmentioning
confidence: 99%
“…Erste Studien, z. B. durch Verabreichung von Probiotika an die Schwangeren, die mütterliche Darmflora zu beeinflussen, befinden sich auf dem Weg [67]. Eine Impfung der Frauen gegen GBS, die für Schwangere und Neugeborene zweifelsohne die beste Lösung darstellen würde, befindet sich nach wie vor im Stadium der Entwicklung [68,69].…”
Section: Fazit Ausblickunclassified